The potential role of purinergic signaling in cancer therapy: perspectives on anti-CD73 strategies for prostate cancer - Gardani, Carla Fernanda Furtado; Diz, Fernando Mendonça; Dondé, Luísa Brandalise; Rockenbach, Liliana; Laufer, Stefan; Morrone, Fernanda Bueno (Frontiers in Immunology, 2024)
Purines and pyrimidines are signaling molecules in the tumor microenvironment that affect cancer immunity. The purinergic signaling pathways have been shown to play an important role in the development and progression of cancer. CD39 and CD73 are ectonucleotidases responsible for breaking down ATP or ADP into adenosine, which regulates immunosuppression in various types of cancer. These enzymes have been studied as a potential therapeutic target in immunotherapy, and recent research suggests a correlation between ectonucleotidases and clinical outcomes in cancer.Prostate cancer is the most diagnosed cancer in men, after non-melanoma skin tumors, and is the second leading cause of death in men in the world. Despite having long survival periods, patients often receive excessive or insufficient treatment. Within this complex landscape, the adenosine/CD73 pathway plays a crucial role. Therefore, this review aims to highlight new findings on the potential role of purinergic signaling in cancer treatment and emphasizes the importance of anti-CD73 as a pharmacological strategy for prostate cancer therapy.